Utilizing interactive media in culinary arts education to enhance student learning outcomes - Erli Mutiara; Ajeng Inggit Anugerah; Dian Agustina Dalimunthe; Siti Sutanti; Rossy Luckita Sasmita; Reni Fitria; Nikmat Akmal (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
This study aims to (1) Develop interactive Flash 8-based learning media for the Introduction to Culinary Arts course, (2) Evaluate the feasibility of this learning media, and (3) Assess students' acceptance of the developed media. The research was conducted in the Culinary Arts Education Study Program at the State University of Medan from June to August 2023. The methodology used was research and development (R&D) with the ADDIE development model, comprising the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 30 students, and the media was validated by two subject matter experts and two media experts. Data collection instruments included a questionnaire to assess material quality, media quality, and student media acceptance. Data were analyzed descriptively. The results indicate that the Flash 8-based media for the Introduction to Culinary Arts course is highly feasible for use, with material validation by experts at 98.33% (very good category) and media validation at 90.57% (very good category). The overall feasibility score averaged 94.52%, indicating a